2010
DOI: 10.1111/j.1750-3841.2010.01573.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of l‐Ascorbic Acid and Ascorbic Acid Oxidase in Broccoli (Brassica oleracea var. italica)

Abstract: The results reported in this study are applicable for both domestic and industrial processing of vegetables into products such as juices, soups, and purees. In this report, we have demonstrated that processing crushed broccoli in a temperature range of 30 to 60 degrees C could result in the conversion of l-ascorbic acid to dehydroascorbic (DHAA), a very important reaction in regard to vitamin C degradation because DHAA could be easily converted to other compounds that do not have the biological activity of vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 26 publications
5
64
1
1
Order By: Relevance
“…5; from the comparison between the two isorate contour plots it is clear that AAO is more heat sensitive than L-AA. Similar trend has been identified regarding the AAO and L-AA in the case of whole broccoli florets blanching, while in the case of crashed florets treatement L-AA found to be also thermosensitive (Munyaka et al, 2010). This can be considered as a key tool to select blanching conditions, optimum blanching processing of mango would require the highest possible inactivation of AAO while maintaining the maximum possible L-AA content.…”
Section: Cuntreatedsupporting
confidence: 50%
See 4 more Smart Citations
“…5; from the comparison between the two isorate contour plots it is clear that AAO is more heat sensitive than L-AA. Similar trend has been identified regarding the AAO and L-AA in the case of whole broccoli florets blanching, while in the case of crashed florets treatement L-AA found to be also thermosensitive (Munyaka et al, 2010). This can be considered as a key tool to select blanching conditions, optimum blanching processing of mango would require the highest possible inactivation of AAO while maintaining the maximum possible L-AA content.…”
Section: Cuntreatedsupporting
confidence: 50%
“…As reported, AAO present in fruits is detected in the cell wall, in the extracellular matrix and in the vacuole and therefore intact cell structure protects AAO from thermal inactivation and leaching (Munyaka et al, 2010). In a recent study regarding mango matrices it was also observed that AAO in whole pieces of mango was in some extent heat resistant and a part of remaining activity was observed after processing (Guiamba, 2016).…”
Section: Ascorbic Acid Oxidase Thermal Inactivation and L-ascorbic Acmentioning
confidence: 78%
See 3 more Smart Citations